2012
DOI: 10.1021/bm3007083
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Poly(methacrylamide) Derivatives Prepared via Aqueous RAFT Polymerization Exhibit Biocidal Efficiency Dependent upon Cation Structure

Abstract: Antimicrobial peptides (AMPs) show great potential as alternative therapeutic agents to conventional antibiotics as they can selectively bind and eliminate pathogenic bacteria without harming eukaryotic cells. It is of interest to develop synthetic macromolecules that mimic AMPs behavior, but that can be produced more economically at commercial scale. Herein, we describe the use of aqueous reversible addition-fragmentation chain transfer (RAFT) polymerization to prepare primary and tertiary amine-containing po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 36 publications
2
80
1
Order By: Relevance
“…DMAm [348] DMAm-b-HEAm [348] 97 n ϭ 1 or 2 [349,350] DEAEMA [351] DMAEMA [350,352] PEGMA [224,[353][354][355] (412) [243] PAA [356] DMAm [326] DMAm [326] HPMAm [357] 357 [357] MAA/PEGMA [354] APMAm/DEAPMAm [358] APMAm/DMAPMAm [358] DEAEMA-bNIPAm [351] DMEAEMA-b-NIPAm [359] PEGMA/MAA-b-St [354,360] PEGMA/MAA-bBzMA [361] PEGMA/MAA-b-327 [362] PAA-bDMAm/408 [356] DMAEMA-b-(PAA/BMA/ DMAEMA) [350,352] HPMAm/450/451 [363] HPMAm-b-357 [357] 98 [364] 317 [311] 332 [365] 333 [365] DMAm [366] BA [366] 350 [311] NIPAm [366,367] MAA/ MMA [368] MAA/DFHA [369] OeMA/MMA [364] 332-b-MMA [365] 333-b-MMA [365] NIPAm-bDMAEAm [367] 99…”
mentioning
confidence: 99%
“…DMAm [348] DMAm-b-HEAm [348] 97 n ϭ 1 or 2 [349,350] DEAEMA [351] DMAEMA [350,352] PEGMA [224,[353][354][355] (412) [243] PAA [356] DMAm [326] DMAm [326] HPMAm [357] 357 [357] MAA/PEGMA [354] APMAm/DEAPMAm [358] APMAm/DMAPMAm [358] DEAEMA-bNIPAm [351] DMEAEMA-b-NIPAm [359] PEGMA/MAA-b-St [354,360] PEGMA/MAA-bBzMA [361] PEGMA/MAA-b-327 [362] PAA-bDMAm/408 [356] DMAEMA-b-(PAA/BMA/ DMAEMA) [350,352] HPMAm/450/451 [363] HPMAm-b-357 [357] 98 [364] 317 [311] 332 [365] 333 [365] DMAm [366] BA [366] 350 [311] NIPAm [366,367] MAA/ MMA [368] MAA/DFHA [369] OeMA/MMA [364] 332-b-MMA [365] 333-b-MMA [365] NIPAm-bDMAEAm [367] 99…”
mentioning
confidence: 99%
“…Cationic polymers are commonly reported as bactericidal materials, [8][9][10][11] although small changes in structure and dose can result in significant differences in activity and toxicity. This effect is often microbe specific, and in particular P1 has been reported to have a minimum inhibitory concentration of 10-25 μg/mL for Escherichia coli, 30 while showing no effect on V. harveyi's viability and growth at concentations as high as 500 μg/mL. 27 Viability in V. cholerae was therefore analysed by monitoring the effect of P1 in bacterial proliferation and viability under physiological conditions.…”
Section: Resultsmentioning
confidence: 99%
“…42,43 Based on this we decided to investigate whether this regulation was unique for P1, or other cationic polymer could trigger the same response in V. cholerae. Primary amine containing polymer P2 30 (Fig. 5) was thus prepared from commercially available N-(3-aminopropyl)methacrylamide hydrochloride, using a similar experimental procedure (see ESI: section 4.2, Fig.…”
Section: Cc-by 40 International License Not Peer-reviewed) Is the Aumentioning
confidence: 99%
“…16 In a direct comparison of different side chain length /archit ecture s it was found that more hydrophobic monomers require a higher amount of cationic comonomer in order to be effective/selective, and for methacrylate based polymers, the methyl side chain was identified to achieve the highest selectivity when the amphiphilic balance is matched, 19 which also holds true when tertiary amines are used as a hydrophobic component (dimethylamine vs. diethylamine). 20 It becomes obvious how fragile that balance is when small changes in the backbone architecture (met hacy lami de inste ad of methacylate) require much higher ratios of hydrophobic comonomer to work. 16 Detailed investigations on quarternized poly (vinyl pyridine)/ methacrylate copolymer systems revealed that one alkyl chain per quarternized amine obtains the best results, and that butyl chain perform best in this type of system.…”
Section: Poly(methacrylate)smentioning
confidence: 99%
“…19 Studies on polymers containing both primary and tertiary amines showed a significant decrease in MIC with increased primary amine fraction. 20 A reason for the superior membrane interaction of primary amines could be the reversibility of the charge, enabling local adjustments in terms of amphiphilicity, which is not possible for quarternary amines.…”
Section: Nature Of the Charged Unitmentioning
confidence: 99%